MONITORING DAN EVALUASI PROGRAM KJP PLUS WILAYAH JAKARTA TIMUR PROVINSI DKI JAKARTA TAHUN 2018 - Rachmat, Ikbal; Rahman, A.; Sumartono, Sumartono; Humaira, Sahira (Jurnal Pengabdian Masyarakat AbdiMas, 2019)
AbstractMonitoring and Evaluation of KJP Plus is carried out as a Community Service (P2M) activity that is established between the Communication Sciences faculty of Esa Unggul University and the Provincial Government of DKI Jakarta, with the aim of conducting verification in the form of data deepening to various parties related to KJP Plus activities from the SD level , Junior high, high school, to the neighborhood where the student / i is concerned. Monitoring and evaluation activities are carried out using a qualitative approach using survey design with the aim of descriptive and non-participatory observation through interviews, with sampling techniques, stratified random sampling of KJP Plus populations in several areas of East Jakarta from each of the Stakeholders (authorized / related parties) namely as many as 6 people consisting of: students, homeroom teachers, school principals, KJP Plus operators, student guardians and RT. The results obtained that this distribution program has been right on target to the recipient, with a note in the form of no increase in achievement for recipient students, lack of special staff KJP Plus program for schools, the unavailability of scanners and the burden on schools with operational costs of visitation to the recipient's home program KJP Plus assistance. Another finding was that the physical forgery of the residence had occurred (at the elementary level recipient) but had been handled before the funding was given. Keywords : Monitoring and evaluation, KJP plus 2018, east jakarta region. AbstrakMonitoring dan Evaluasi KJP Plus dilakukan sebagai kegiatan Pengabdian Pada Masyarakat (P2M) yang terjalin antara fakultas Ilmu Komunikasi universitas Esa Unggul dan Pemerintah Provinsi DKI Jakarta, dengan tujuan melakukan verifikasi berupa pendalaman data-data kepada berbagai pihak yang terkait dengan kegiatan KJP Plus dari Tingkat SD, SMP, SMA, hingga lingkungan tempat tinggal siswa/i yang bersangkutan. Kegiatan monitoring dan evaluasi dilakukan menggunakan pendekatan kualitatif menggunakan desain survei dengan tujuan deskriptif dan observasi non partisipasi melalui wawancara, dengan teknik sampling, stratified random sampling dari populasi KJP Plus di beberapa wilayah Jakarta Timur dari masing-masing Stakeholder (pihak yang berwenang/terkait) yakni sebanyak 6 orang yang terdiri dari : siswa/i, wali kelas, kepala sekolah, operator KJP Plus, wali murid dan RT. Hasil yang diperoleh bahwa program penyaluran ini telah tepat sasaran kepada penerimanya, dengan catatan berupa tidak adanya peningkatan prestasi bagi siswa/i penerima, kurangnya tenaga khusus program KJP Plus bagi pihak sekolah, belum tersedianya scanner serta terbebaninya sekolah dengan biaya operasional visitasi ke rumah penerima program bantuan KJP Plus. Temuan lainnya terdapat upaya pemalsuan fisik tempat tinggal sempat terjadi (pada penerima tingkat SD) namun telah tertangani sebelum pemberian dana. Kata kunci : Monitoring dan evaluasi, KJP plus 2018, wilayah jakarta timur.